1998
DOI: 10.1046/j.1365-2923.1998.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of tutors' content expertise to interventions and perceptions in a PBL medical curriculum

Abstract: This study addressed three questions: (1) Do content-expert tutors differ from non-expert tutors in the extent to which they present/explain case content? (2) Do tutors who present/explain case content differ from those who almost never do in their ratings of various outcomes of a PBL curriculum? (3) Are tutors who present/explain case content rated differently by students from tutors who almost never do? Data were gathered from 88 tutors and 168 students in the first 2 years of a PBL medical curriculum. Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 11 publications
2
35
1
1
Order By: Relevance
“…Content expertise seems to result in a more directive role on the part of tutors and in fewer student-student interactions. The results of these studies also correspond with a study conducted by Kaufmann & Holmes (1998). These researchers found that tutors who rated themselves as content experts found it difficult to maintain the facilitator role and tended to present and explain case material more frequently than tutors who had less content expertise.…”
Section: Trend 2: Studies On Process Variablessupporting
confidence: 83%
“…Content expertise seems to result in a more directive role on the part of tutors and in fewer student-student interactions. The results of these studies also correspond with a study conducted by Kaufmann & Holmes (1998). These researchers found that tutors who rated themselves as content experts found it difficult to maintain the facilitator role and tended to present and explain case material more frequently than tutors who had less content expertise.…”
Section: Trend 2: Studies On Process Variablessupporting
confidence: 83%
“…As in our own study, other research has found that the biggest risk in having clinicians facilitate small groups is a tendency to take over the group process either by directly questioning students (Gilkison, 2003;MacPherson et al, 2001;Silver and Wilkerson, 1991) or by teaching rather than encouraging student discovery and learning (Kaufman and Holmes, 1998;Wilkerson and Irby, 1998). Other problems with tutors identified in our study and the literature also points to inadequate amounts of guidance and feedback they give to students (O'Hanlon et al, 1995).…”
Section: Discussionsupporting
confidence: 61%
“…Tossing back was a straightforward but useful technique that facilitators could use when they did not want to be seen as "content experts. " Research showed that such an expert role had a detrimental effect on group discussion (Kaufmann & Holmes, 1998). Participants were less willing to contribute ideas when they considered their facilitator experts.…”
Section: Checking For Interpretationmentioning
confidence: 99%